2020
DOI: 10.1177/0363546520964479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Patients With Anterior Shoulder Instability and Glenolabral Articular Disruption Lesions: A Retrospective Comparative Study

Abstract: Background: Anterior shoulder instability is a common clinical condition that often requires surgical stabilization. Glenoid labral tears are often associated with instability, with glenolabral articular disruption (GLAD) lesions occasionally being identified arthroscopically during repair, particularly in collision athletes. Purpose: To evaluate the clinical outcomes and recurrence rates in patients who had GLAD lesions and underwent arthroscopic Bankart repair (ABR) and compare them with a control group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Davey et al had a closer look on this assumption and analyzed the effect of a GLAD lesion by means of other patient-reported outcome scores. 24 They identified no significant impact of a GLAD lesion after ABR. However, patients with a GLAD lesion showed a mean subjective shoulder value that was 8 points lower compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Davey et al had a closer look on this assumption and analyzed the effect of a GLAD lesion by means of other patient-reported outcome scores. 24 They identified no significant impact of a GLAD lesion after ABR. However, patients with a GLAD lesion showed a mean subjective shoulder value that was 8 points lower compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Any associated labral tear was then repaired arthroscopically using a previously described technique. 5…”
Section: Methodsmentioning
confidence: 99%
“…8 The complexity of the anatomic shoulder stabilizers results in a variety of pathologies in patients with anterior shoulder instability. 3,10,13,14,20,25 Davey et al 5,6 previously reported that the average collision athlete with anterior shoulder instability experiences a multitude of pathologies secondary to recurrent dislocations displayed on preoperative imaging before surgical stabilization, with bony Bankart and Hill-Sachs lesions being the most common. In addition, the humeral avulsion glenohumeral ligament (HAGL) lesion has been shown to occur in up to 10% of cases of recurrent anterior shoulder instability.…”
mentioning
confidence: 99%
“…Rehabilitation after surgical intervention for shoulder instability can be broadly characterized by a few main phasesdprotection, endurance, strength, then return to sport. [61][62][63][64][65] Sling immobilization semioperatively varies significantly across the literature from 0 to 2 weeks, 65,66 3 weeks, 62 4 weeks, 61,67 or even up to 6 weeks. 68 After immobilization, athletes can begin active-assisted and active ROM exercises around 4 to 6 weeks semioperatively.…”
Section: Anterior and Posterior Shoulder Instability Rehabilitation Timelinementioning
confidence: 99%
“…In 66 collision athletes, the return to play rate after arthroscopic Bankart repair was 90.9% at a mean of 6 months. 62 A study of martial art athletes found 95% RTP rate in 6.4 months after arthroscopic Bankart repair. 67 After arthroscopic Bankart repair or open Latarjet reconstruction, 22 of 23 professional athletes were able to return a mean of 4.5 months after surgery.…”
Section: Return To Playmentioning
confidence: 99%